Analisis Faktor Penghambat Berpikir Kreatif Pada Siswa Dalam Pembelajaran IPAS - Lestari, Reni; Lingga, Leny Julia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to determine the factors inhibiting creative thinking in students in learning science and science in the independent curriculum for class IV SDN 022 Muara Langsat. The research method used is a qualitative method with a descriptive approach with data collection techniques namely interviews, observation, questionnaires and documentation. The subjects of this research were class IV students consisting of 25 students and 1 homeroom teacher, and data collection instruments in the form of interview guidelines, observation guidelines, questionnaires, and documentation review. The data analysis technique uses the Miles and Huberman Model which consists of data collection, data reduction, data presentation and conclusions. The results of the research questionnaire showed that there was 21,8% reaching level 4 (very creative), 31,4% reaching level 3 (creative), 36,6% reaching level 2 (quite creative), and 10,2% reaching level 1 (less creative).